A method for predicting subsurface fatigue life of rolling bearings based on macro–micro coupling model. (June 2022) - Li, Chang; Chen, Zhengwei; Liu, Zhaotai; Han, Xing; Chen, Xinxue
The fatigue life of the bearing can be predicted effectively by combining the multifield coupling condition of the working process with the internal microstructure. In this paper, a bearing fluid lubrication model is established based on the computational fluid dynamics method, and the calculation result is coupled to the thermal-solid model by the grid mapping method. Through this method, a bearing thermal-fluid-solid multifield coupling dynamics model is established to obtain the evolution information of bearings. Simultaneously, the micro-characterization experiments of SKF6406 bearing (M50 bearing steel) were carried out by electron backscatter diffraction, scanning electron microscope and nano-indentation. The microstructure model of bearing containing micro-inclusions was established by the Voronoi method. On this basis, the microscopic stress distribution characteristics and the motion law of bearing microstructure under the multifield coupling action are solved. In the end, the fatigue life prediction method of rolling bearing was established.